Smart Concretes: Review - Khitab, A; Alam, M; Riaz, H; Rauf, S (International Journal of Advances in Life Science and Technology, 2014)
Concrete is a versatile and the most widely used material in the world. According to a recent survey, its annual production is one cubic meter per person. Historically, it is an old material, which has evolved tremendously during the passage of time. This paper envisages the most recent smart developments in this wonderful material. The smart concretes discussed in this paper include Engineering Cementitious Composites, Self cleaning concrete, self heating concretes and ultra high performance powder reactive concretes. Through modern technology, the strength of concrete has been enhanced from a few hundred pounds per square inch to more than 30000 pounds per square inch. In the same way, the utility of concrete has been tremendously broadened in many fields. Here, primarily, a brief introduction of all important recent developments is discussed. Next, the composition of these materials is narrated, followed by their applications and utilities. The main theme of this paper is to understand the importance of these concretes and to introduce it to academia and construction industry of Pakistan. It is demonstrated that the introduction of these materials will solve many problems of construction, which are not possible to solve with conventional means. Moreover, these developments could solve many energy problems and some are even quite suitable for earthquake zones of Pakistan.